Primary cardiac lymphoma - Kapur,B; Nair,R; Gopal,R; Abhyankar,D; Naresh,K; Laskar,S; Muckaden,M; Advani,S (Indian Journal of Hematology and Blood Transfusion, 2000)
Primary cardiac lymphoma is a rare disease. We report a case of lymphoma of right and ventricle who was treated with multimodality treatment and remains in complete remission 18 months after treatment completion.